High-throughput reformatting of phage-displayed antibody fragments to IgGs by one-step emulsion PCR. Issue 11 (9th April 2019) - Liu, Yaohui; Gu, Manping; Wu, Yaxing; Wang, Wei; Wang, Ruikun; Du, Mingjuan; Ma, Peixiang; Zhou, Xingdong; Wang, Yuan; Cao, Youjia; Zhang, Hongkai
Abstract: Single-chain variable fragment (scFv) is the most common format for phage display antibody library. The isolated scFvs need to be reformatted to full-length IgGs for further characterization. High throughput reformatting of scFv to IgG without disrupting VH–VL pairing is of great demanding for exhaustive screening of all antibodies in IgG format. Herein, we developed a strategy based on the overlap extension PCR in emulsion to reformat scFv to IgG while maintain the accuracy and complexity of variable region pairing. Using CD40 as an example target, we reformatted phage display derived CD40 binding scFv library to IgG mammalian display library and isolated high affinity CD40 binding IgGs. This robust and reliable antibody reformatting approach could be integrated into any phage display based antibody drug discovery.